Pengembangan Media Pop-Up Book Interaktif Berbasis Power Point Desain Canva untuk Meningkatkan Kearifan dan Hasil Belajar Siswa melalui Teks Deskripsi Berorientasi pada Tradisi Botram Suku Sunda - Luluk Nikmahtul Sya’diyah; Nurul Istiq’faroh; Jihan Munawaroh (Journal of Contemporary Issues in Primary Education, 2026)
This study aims to develop an interactive pop-up book learning media based on PowerPoint with Canva design, oriented toward local wisdom of the botram tradition of the Sundanese culture, to improve students’ understanding and learning outcomes in descriptive text learning. This research employed a quantitative descriptive method using a one-group pretest-posttest design. The subjects were third-grade elementary school students. Data were collected through cognitive tests (pretest and posttest) and a student response questionnaire consisting of 30 items. Data analysis techniques included normality tests, paired sample t-tests, and N-gain analysis. The results showed that the data were normally distributed, with pretest and posttest significance values above 0.05. The paired sample t-test indicated a significance value of less than 0.01, meaning there was a significant difference in student learning outcomes before and after treatment. The effect size (Cohen’s d) was -1.653, categorized as very large. Meanwhile, the N-gain score was 0.3040, indicating a moderate level of improvement. In conclusion, the developed interactive pop-up book media is effective in enhancing students’ learning outcomes, although the level of improvement is moderate. This media is expected to serve as an innovative and contextual learning resource integrating local cultural values.